Multi-Criteria Evaluation of Quality of Exisiting Urban Parks in Dhaka City - Towards Achieving Livable City - Neema, MN; Hossain, MR; Haque, AM; Farhan, MHM (International Journal of Environment, 2014)
Qualitative and quantitative assessment of the quality of major parks in mega city Dhaka have been conducted. Four incommensurate factors: environment, safety and security, landscape and aesthetic value have been considered to qualitatively and quantitatively assesses the quality of the parks. From qualitative analysis it is found that, some parks (located in highly classified residential area of the city) are superior in safety and security and landscape design whereas other parks (located remote from residential area) are inferior in safety and security and environmental factor. It is necessary to address factors of each park lacking behind to ensure better quality of parks. To quantitatively assess the quality of parks, we formulated a new index value calculation to rank all parks in terms of all factors. It is found that the quality of all the parks are dispersed. In addition, investigation of universal accessibility of the parks and direct park user’s opinion has been accumulated to supports findings of this analysis. Based on the major findings of this study a number of recommendations have been provided for the improvement of the quality of parks in Dhaka city such as involvement of local community and establishment of office for the park authority inside the park can be helpful in the quality maintenance of the parks. The findings of this paper can enhance the existing knowledge of city planners a step forward with a-priori knowledge to ensure quality of parks in further city planning. DOI: http://dx.doi.org/10.3126/ije.v3i3.11058 International Journal of Environment Vol.3(3) 2014: 1-15